2004
DOI: 10.1213/01.ane.0000099715.40831.2a
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypoxemia During One-Lung Ventilation Using Intravenous Almitrine

Abstract: IV almitrine improves oxygenation during one-lung ventilation without hemodynamic modification. Such treatment could be used when conventional ventilatory strategy fails to treat hypoxemia or cannot be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Transoesophageal Doppler is not appropriate as a characteristic aortic blood flow signal cannot be obtained in half of the patients in similar conditions. 24 Consequently, we could not have any access to cardiac output evaluation. However, requirements for ephedrine, heart rate, and mean arterial pressure were similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Transoesophageal Doppler is not appropriate as a characteristic aortic blood flow signal cannot be obtained in half of the patients in similar conditions. 24 Consequently, we could not have any access to cardiac output evaluation. However, requirements for ephedrine, heart rate, and mean arterial pressure were similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Despite treatment with nitric oxide [3], prostaglandin E1 [4], prostaglandin F2 alpha [5], almitrine [6], or different anesthetic drugs [7][8][9][10], hypoxemia during OLV can remain a problem.…”
Section: Introductionmentioning
confidence: 99%
“…Length of hospital stay was 15 (10), 17 (11) and 12 (3) days for the placebo, ALM4+NO and ALM16+NO groups respectively, and intrahospital mortality was 0/14, 1/14 and 0/14 respectively. No clinical signs of Silva-Costa-Gomes et al (8) polyneuropathy were observed in any patient at the time of discharge.…”
Section: Resultsmentioning
confidence: 70%
“…[3][4][5] Almitrine enhances hypoxic pulmonary vasoconstriction (HPV) in non-ventilated lung units, while iNO dilates pulmonary vessels from the ventilated areas. Regarding OLV, only one group of investigators demonstrated that almitrine alone or combined with iNO improved hypoxia, [6][7][8] but the optimal dose of almitrine, combined with iNO during open-chest OLV, that would provide improvement in oxygenation with minimal sideeffects is unknown. The present investigation was designed to address this issue.…”
mentioning
confidence: 99%